2017
DOI: 10.1186/s12884-017-1285-9
|View full text |Cite
|
Sign up to set email alerts
|

Midwife-led maternity care in Ireland – a retrospective cohort study

Abstract: Background: Midwife-led maternity care is shown to be safe for women with low-risk during pregnancy. In Ireland, two midwife-led units (MLUs) were introduced in 2004 when a randomised controlled trial (the MidU study) was performed to compare MLU care with consultant-led care (CLU). Following study completion the two MLUs have remained as a maternity care option in Ireland. The aim of this study was to evaluate maternal and neonatal outcomes and transfer rates during six years in the larger of the MLU sites. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(37 reference statements)
2
13
1
2
Order By: Relevance
“…The intrapartum transfer rate of the Cocoon women lies within the intermediate range. In the literature, transfer rates vary from 12% to 31.3% . In their study of 16 710 patients, the Birthplace in England Collaborative Group found a transfer rate from an alongside midwifery unit of 21.2% before delivery .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrapartum transfer rate of the Cocoon women lies within the intermediate range. In the literature, transfer rates vary from 12% to 31.3% . In their study of 16 710 patients, the Birthplace in England Collaborative Group found a transfer rate from an alongside midwifery unit of 21.2% before delivery .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, transfer rates vary from 12% 20 to 31.3%. 2,12,16,[20][21][22] In their study of 16 710 patients, the Birthplace in England Collaborative Group found a transfer rate from an alongside midwifery unit of 21.2% before delivery. 12 Nulliparous women were more likely to be transferred from a non-obstetric unit setting to an obstetric unit (36 to 45%) than multiparous women (9%-13%).…”
Section: Discussionmentioning
confidence: 99%
“…3,[17][18][19][20][21] There are also several observational studies into AMUs, with comparison OU outcomes. 19,22,23 The limited contemporary research into the comparative clinical outcomes for FMUs and OUs includes prospective studies, [24][25][26] a retrospective study 27 and population-based cohort studies. 19,28 There are also studies reporting only MU clinical outcomes, with no OU comparison outcomes from the same context.…”
Section: Updated Literature Reviewmentioning
confidence: 99%
“…Several researchers have argued that the empirical evidence about risk in MNC that is often used to inform policy is not objective, but interpreted through the lens of one's beliefs and interests (see, for example, Dencker, Smith, McCann, & Begley, 2017;de Vries, Paruchuri, Lorenz, & Vedam, 2013;Healy, Humphreys, & Kennedy, 2016b;Lane, 2015;Roome, Hartz, Tracy, & Welsh, 2016). Studies have also shown that use of medical interventions in MNC is associated with provider attitude rather than evidence, resulting in undesired practice variation and negatively affecting care outcomes (Klein et al, 2009;Offerhaus et al, 2015;Rivo et al, 2018;White VanGompel, Main, Tancredi, & Melnikow, 2018).…”
Section: The Politics Of Risk In Boundary Workmentioning
confidence: 99%